2008
DOI: 10.1016/j.childyouth.2007.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparing outcomes for youth in treatment foster care and family-style group care

Abstract: Group care programs are often criticized for producing poor outcomes, especially in light of community-based alternatives like treatment foster care that have a stronger evidence base. In this study, data from Girls and Boys Town were used to compare outcomes of youth in treatment foster care (n=112) and group care (n=716) using propensity score matching, a method that can minimize selection bias in nonrandomized designs. Eighteen background covariates were used to develop propensity scores for the likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 46 publications
3
85
1
Order By: Relevance
“…Similar outcomes are evident for juvenile offenders (Larzerene et al 2004;Kirigin 2001). Lee and Thompson (2008) report an increase in educational attainment, positive adult-youth relationships, and decreases in re-arrest rates for youth served in teaching-family homes over those served in residential programs.…”
Section: Family and Institutional Caresupporting
confidence: 54%
“…Similar outcomes are evident for juvenile offenders (Larzerene et al 2004;Kirigin 2001). Lee and Thompson (2008) report an increase in educational attainment, positive adult-youth relationships, and decreases in re-arrest rates for youth served in teaching-family homes over those served in residential programs.…”
Section: Family and Institutional Caresupporting
confidence: 54%
“…The review included only two-group outcomes studies so the effects of a group care placement could be compared to an alternative service, which is a stronger research design than the more commonly published single group studies. Overall results suggested the most positive effects for family-centered group care models (Landsman et al 2001), Teaching-Family group care (Lee and Thompson 2008;Thompson et al 1996) and multi-dimensional treatment foster care (MTFC; Chamberlain et al 2007;Chamberlain and Reid 1998). The practice components that are emphasized in these more effective group care models include family involvement, family-style living, adult supervision and behavior monitoring, positive reinforcement, limit setting, and social skills training.…”
Section: Previous Efforts To Differentiate Group Carementioning
confidence: 88%
“…Just as ''in-home'' services like wrap around and multi-systemic therapy have some overlapping elements but are not identical-and may have quite different results (Stambaugh et al 2007)-the same is likely to be true for group care. Research that indicates, in general terms, that ''group care'' appears to offer no additional overall benefit for the average youth (see, e.g., Barth et al 2007;Chamberlain and Reid 1998;Ryan et al 2008) has to be tempered by evidence that some group care has better results on some dimensions than treatment foster care (Lee and Thompson 2008). Tools to minimize over generalizing across programs with different intervention components and goals offer the field more precision in determining which studies of group care provide information relevant to which program models or elements work what youth.…”
Section: Importance Of Differentiating Group Care Programsmentioning
confidence: 96%
“…While studies evaluating the direct benefits of residential care are mixed (Curry 1991;Lee and Thompson 2008), the literature evaluating long-term outcomes post-discharge reveals a discouraging picture of academic failure and economic and social emotional struggles (CWLA 2005b;Lyons et al 2001). For example, a recent study reported findings of youth from residential group care and therapeutic foster care at 6, 12, and 24 months postdischarge.…”
Section: Outcomes and Impactmentioning
confidence: 98%